Educação ambiental e o uso de agrotóxicos - Fassis, Fabiana [UNESP] (2014)
In this work, we turn our attention to subjects involved in educational activities related to environmental issues in a community where the use of pesticides is present indiscriminately. Thus, our search has taken place towards the construction of possible senses based on the statements of different social characters in this community about the relation between intensive use of pesticides, environmental education and opportunities for political education and empowerment. We seek to discuss examples of society relation - hegemonic nature in contemporary society and the role of education and, more specifically, environmental education processes of the social examples transformations. We assume that education has given priority to human development and therefore assumes its political and emancipatory character building citizenship. The relationship between the educational process and the intensive use of pesticides is chosen as a matter of study and, therefore, we look to explore the main aspects that have been considered by the environmental debate on this issue. The cultural historical approach guided the processes of collection, systematization and analysis of data. The analytical process allowed us to build four cores of meaning, namely: 1) Model of agricultural production and the use of pesticides; 2) Emphasis and appreciation of the knowledge dimension in the educational process; 3) Emphasis on perspectives that point to pedagogical optimism or illusion; 4) Emphasis on the relationship between education and the world of work. From the dialogue between the literature and other researches in the field of environmental education, latent themes related to these core meanings were discussed and investigated as to their meaning for educational processes related to the formation of citizenship